Modeling Response to Repetitive Marketing Stimuli - Fox, Richard J. (Institutional Knowledge at Singapore Management University, 1997)
Marketers frequently include promotional stimuli which elicit some form of response from the recipient among the tactics used to market products or services. Print ads, including 800 numbers which allow consumers to respond, and direct mail campaigns are examples of such activities. Promotions of this nature are often repeated a number of times, thus providing several opportunities to respond. Understanding consumer response to such campaigns is critical for more efficient design and use of these activities. A conceptual framework of response to repetitive stimuli is proposed, and stochastic models of alternative response patterns are developed. Alternative contexts in which such models are useful are also noted. Variations of the models are provided for those situations when only a fraction of the target population will ever respond. Estimation of model parameters is discussed, and data from actual campaigns are used to demonstrate how to apply the models.